2012
DOI: 10.18055/finis1649
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de um microerosómetro do tipo TMEM para aplicação em plataformas rochosas litorais

Abstract: Resumo -A determinação da taxa de erosão das plataformas rochosas litorais necessita de equipamento específico, adaptado às condições ambientais em que se desenvolvem estas plataformas. Neste trabalho, descreve-se a concepção de equipamento adaptado a esse fim -um microerosómetro do tipo TMEM (Traversing Micro-Erosion Meter) -ao qual foram introduzidas algumas modificações, que visam melhorar quantitativa e qualitativamente os dados a obter. São também indicados, para além das vantagens e limitações deste equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…The value for biocalcarenite downwearing measured in our work is similar to that observed by several other authors for limestone in shore platforms between 0.034 and 0.400 mm year − 1 (Neves et al, 2001, Cucchi et al, 2006, Swantesson et al, 2006a, Furlani et al, 2010 whereas lowering rates in calcarenite and siltstone fall within values reported by other works for detrital rocks: (i) siltstone: 1.8 mm/year − 1 (Gill and Lang, 1983), (ii) sandstone: 1.254 mm/year − 1 (Porter et al, 2010), and (iii) greywacke: 0.300-0.405 mm/year − 1 (Gill and Lang, 1983). That difference between carbonate and more detrital rocks is likely to be related to mass properties like fabric and porosity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The value for biocalcarenite downwearing measured in our work is similar to that observed by several other authors for limestone in shore platforms between 0.034 and 0.400 mm year − 1 (Neves et al, 2001, Cucchi et al, 2006, Swantesson et al, 2006a, Furlani et al, 2010 whereas lowering rates in calcarenite and siltstone fall within values reported by other works for detrital rocks: (i) siltstone: 1.8 mm/year − 1 (Gill and Lang, 1983), (ii) sandstone: 1.254 mm/year − 1 (Porter et al, 2010), and (iii) greywacke: 0.300-0.405 mm/year − 1 (Gill and Lang, 1983). That difference between carbonate and more detrital rocks is likely to be related to mass properties like fabric and porosity.…”
Section: Discussionsupporting
confidence: 92%
“…To further investigate the importance of porosity, we parameterized data from our study and from other published data (Gill and Lang, 1983;Spencer, 1985;Stephenson and Kirk, 1998;Neves et al, 2001;Andrade et al, 2002;Swantesson et al, 2006a;Blanco-Chao et al, 2007;Stephenson et al, 2010) concerning rock texture, instead of grouping them in the conventional way by lithological composition. Our parameter attribution was based on general concepts such as: (i) crystalline rocks are less porous than sedimentary rocks; (ii) finegrained rocks are less permeable than coarse-grained sedimentary rocks; and (iii) the texture of rocks with large fossils is more heterogeneous (i.e., more porous) than those containing microfossils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous studies reporting platform surface lowering, measured using the micro-erosion meter (MEM) or traversing microerosion meter (TMEM) (Trudgill, 1976;Kirk, 1977;Robinson, 1977a,b, c;Spencer, 1981;Gill and Lang, 1983;Spencer, 1985;Shakesby and Walsh, 1986;Kirk, 1998, 2001;Neves et al, 2001;Inkpen et al, 2004;Cucchi et al, 2006;Foote et al, 2006;Gomez-Pujol et al, 2006). These studies usually measured erosion over periods of about two years.…”
Section: Introductionmentioning
confidence: 99%
“…A common method used to measure changes in the surface of the shore platform has been the micro-erosion meter (MEM) or the traversing micro-erosion meter (TMEM) (Trudgill, 1976;Kirk, 1977;Robinson, 1977a,b,c;Spencer, 1981Spencer, , 1985Gill and Lang, 1983;Shakesby and Walsh, 1986;Kirk, 1998, 2001;Neves et al, 2001;Inkpen et al, 2004;Cucchi et al, 2006;Foote et al, 2006;Gomez-Pujol et al, 2006;Inkpen and Stephenson, 2006). Usually these studies measure rates over a two-year period, although recent studies have also used these instruments to monitor rates of surface change over a few days or a few hours (e.g.…”
Section: Introductionmentioning
confidence: 99%